Media and the War on Terror: A Case Study of Islamic News Magazine Reporting in the Transition Indonesia - Prayudi - (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
This research looks at the representation of recent terrorist attacks in Indonesian Islamic news media within a context of cultural and social transition. It is based on an understanding that modern terrorism is formed in relation to the media and global networked media systems. Terrorism can be considered to be a stage upon which political ‘drama’ is performed for specific audiences, (national or international publics, particular groups or individuals, or political elites). In this context, the news media play a crucial role in distributing the message to the audience. At the same time, the way the news media represent the issue is influenced by the cultural, political, economic and social conditions in which the political violence is being played out.